Impact of the temperament of Nellore cows on the quality of handling and pregnancy rates in fixed-time artificial insemination - Rueda, Paola M. [UNESP]; Sant'Anna, Aline C. [UNESP]; Valente, Tiago S. [UNESP]; Paranhos da Costa, Mateus J. R. [UNESP] (Elsevier B.V., 2015)
The aim of this study was to evaluate the effects of temperament on the quality and efficiency of handling and on the pregnancy rate of Nellore cows submitted to a fixed time artificial insemination (FTAI) protocol. Temperament and handling procedures were simultaneously assessed in 798 Nellore cows on the first (d0), ninth (d9) and 11th days (d11) of the FTAI protocol, using the flight speed (FS) and crush score (CS) tests. During the insemination process performed on d11 of the FTAI protocol, the following handling indicators were recorded: rough or overly aggressive handling of the cows by stockpersons (AGGRESSION), accidents (ACCIDENT), time to inseminate (TIME), and the degree of dirtiness on cows'perineal region (DIRTINESS). There was a significant effect of CS on TIME (P=0.013) and DIRTINESS (P=0.004), while FS tended to affect TIME (P=0.06) and the likelihood of AGGRESSION (P=0.07). Cows subjected to aggressive handling and/or accidents had a greater FS mean than cows that did not face such aversive situations (2.07 +/- 1.18 vs. 1.74 +/- 0.75 m/s, P=0.0003). The chance of pregnancy (expressed in odds ratio) was greater in cows with low FS (OR=1.48) than in cows with high FS (defined as the reference class, with OR= 1) (chi(2)=3.73, P=0.05), and the low FS group had 10% more pregnant cows than the high FS group (with 52.59% vs. 42.62% pregnant cows, respectively). Pregnant cows had significantly lower FS means relative to non-pregnant cows on d0 (1.79 vs. 2.10 m/s, P < 0.001), d9 (1.67 m/s vs. 1.79 m/s, P=0.038) and d11 (1.70 m/s vs. 1.90 m/s, P=0.004). We conclude that excitable temperament has an effect on the quality and efficiency of handling during FTAI, by increasing the time required for insemination, the dirtiness on cows'perineal region and the likelihood of aggressive actions by stockpersons. Also, cattle temperament measured by FS reduces the chance of pregnancy in Nellore beef cows. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Behavior; Human-animal relationship; Beef cattle; Reactivity; Reproductive performance